Poverty Reduction during the Rural-Urban Transformation : The Role of the Missing Middle - Christiaensen, Luc (World Bank, Washington, DC, 2013)
As countries develop, they restructure away from agriculture and urbanize. But structural transformation and urbanization patterns differ substantially, with some countries fostering migration out of agriculture into rural off farm activities and secondary towns, and others undergoing rapid agglomeration in mega cities. Using cross-country panel data for developing countries spanning 1980-2004, the analysis in this paper finds that migration out of agriculture into the missing middle (the rural nonfarm economy and secondary towns) yields more inclusive growth patterns and faster poverty reduction than agglomeration in mega cities. This suggests that patterns of urbanization deserve much more attention when striving for faster poverty reduction.